Hubungan Cakupan Imunisasi dengan Kasus Difteri di Provinsi Jawa Timur Tahun 2023 - Eny Qurniyawati; Asma Azzahra; Izzah Nur Shabrina; Fifta Hayu Ananda (Media Gizi Kesmas, 2024)
Background: Diphtheria is an infectious disease caused by the bacterium Corynebacterium diphtheria, which commonly affects body part such as the tonsils pharynx, larynx and nose. Mobility and population density are one of the risks of diphtheria transmission in humans who play a major role as a reservoir of diphtheria bacteria. The number of diphtheria cases in East Java Province in 2022 increased by 1.46 times compared to 2021. The death rate from diphtheria also increased by 0.21 times in 2022 compared to 2021. The number of PD3I (Penyakit yang Dapat Dicegah dengan Imunisasi) case findings will indirectly illustrate the condition of immunization coverage received by the community as an effort to form herd immunity. Objectives: To spatially analyze the distribution of diphtheria cases associated with immunization coverage by district/city in East Java in 2023. Methods: A descriptive analytic approach was conducted through a spatial analysis model that explores data from a spatial perspective. Statistical analysis was also conducted to support the hypothesis of a relationship between the variables studied. Measurement of the strength of the relationship was carried out using the Spearman correlation test (α=0.05) to correlate the immunization coverage variable with diphtheria cases. Results: From the mapping results, it is known that Situbondo district has the lowest immunization coverage (78%) and Bondowoso district has the highest immunization coverage (115%). Statistical tests showed no association between immunization coverage and diphtheria suspects, cases, and findings (p-value > 0,05). Conclusions: The test results showed that there was no association between the two variables. Evaluation and monitoring of immunization implementation focusing on vaccine quality and activation of epidemiological investigation surveillance in East Java Province need to be done to optimize herd immunity in the community.